Prevalence of nasal septal deviation and its effects on concha bullosa, maxillary sinus mucosal thickness, and depth of palatal arch-An observational CBCT study - Syeda Muskan Jan; Balaji Pachipulusu; Poornima Govindraju (Wolters Kluwer Medknow Publications, 2023)
Background: Nasal septum deviation (NSD) is a facial midline deviation of the septum's bone or cartilage, nasal promoting nasal obstruction which results in mouth breathing with implications on lip and tongue position, high arched palate, and decreased nasal permeability, and nasal turbinate hypertrophy causes a reduction in the size of the nasal airways leading to concha bullosa (CB), mucociliary obstructions, and maxillary sinusitis. Objectives: To evaluate the degree and types of NSD, presence of CB and laterality, thickness of maxillary sinus mucosa (TMSM) about NSD and relationship of NSD alone and in conjunction with palatal arch depth. Materials and Methods: One hundred eighty cone beam computed tomographic (CBCT) images were procured from CBCT archives by random sampling method. Results: The prevalence of NSD and CB was found to be 43.3% and 42.2%, respectively. In these studies, males and females showed equal distribution and laterality with the most common being type II deviation. CB showed predominant unilateral CB. Conclusions: Comparison was made between all parameters NSD and CB, NSD and TMSM showed a strong relationship, and maxillopalatal parameters and NSD showed relatively higher values.